The Relationship between Supply Chain Integration and Supply Chain Performance among Logistic Service Provider in Johor - Fazian Hashim; Ida Izyani Misnan (Research in Management of Technology and Business, 2024)
For many years, supply chain integration—the strategic alignment of internal organizational activities and processes—has been a major focus of concern. The precise design of the kind of integration that will result in supply chain performance is a topic of much discussion. This study aimed to determine the ways in which logistics service providers in Johor will benefit from enhanced supply chain performance, including logistics flexibility and operational performance, through two types of integration: internal and supplier integration. 95 workers of a Johor logistics service provider participated in an online survey, with a 66% response rate. Both descriptive analysis and Spearman correlation analysis were used to analyze the data. The results of this study indicated a significant correlation between supply chain performance and supply chain integration.